Microresonator-enhanced quantum dot single-photon emission in GaAs-on-insulator platform - Yueguang Zhou; Yuhui Yang; Imad Limame; Priyabrata Mudi; Marcel Hohn; Claudia Piccinini; Battulga Munkhbat; Yann Genuist; Jean-Michel Gérard; Julien Claudon; Kresten Yvind; Niels Gregersen; et al. (Materials for Quantum Technology)
Single-photon emitters play a crucial role in integrated photonic quantum systems across various material platforms. In this study, we present a cavity-enhanced quantum dot single-photon source in a high-index contrast material platform (GaAs-on-insulator). A quantum dot is embedded in a microring resonator with a quality factor of approximately 9000, where the cavity-induced light enhancement results in a spontaneous emission acceleration factor of around 2.6, and we achieve a $g^{(2)}(0)$ as low as 0.03 ± 0.02 and post-selected two-photon interference visibility of 51.7 $%±3.2%$ for the single-photon source. This demonstration shows the potential of the GaAs-on-Insulator platform for scalable on-chip quantum information processing.